Efficacy of telbivudine compared with entecavir in hepatitis B virus‐related cirrhosis: 2 year follow‐up data. (5th July 2014) - Kim, Hae Rim; Yim, Hyung Joon; Kang, Seonghee; Suh, Sang Jun; Kim, Seung Young; Hyun, Jong Jin; Koo, Ja Seol; Kim, Ji Hoon; Seo, Yeon Seok; Yeon, Jong Eun; Lee, Sang Woo; Byun, Kwan Soo; et al.
Abstract Background & Aims Entecavir (ETV) is effective in the treatment of chronic hepatitis B virus (HBV) infections, even in patients with underlying cirrhosis. However, there is little information on the effect of telbivudine (TBV) in chronic hepatitis B patients with cirrhosis.This study compared the antiviral efficacy of TBV and ETV in HBV‐related cirrhosis. Methods We consecutively enrolled 151 treatment‐naïve patients with HBV‐related cirrhosis who started antiviral therapy with TBV (n = 61) or ETV (n = 90). Results After 24 months of treatment, per‐protocol analysis showed similar virological response rates (HBV DNA <20 IU/ml) in the TBV group (80.6%, 25/31) and in the ETV group (90.2%, 74/82) (P = 0.167). However, intention‐to‐treat analysis showed lower virological response rates in the TBV group (41.7%, 25/60) than in the ETV group (83.1%, 74/89) (P = 0.001). Mean reduction in HBV DNA levels was greater in the ETV group (−3.72 ± 1.94 vs. −4.87 ± 1.57 respectively, P = 0.001). Serologic and biochemical response rates at month 24 did not differ significantly between the groups. Child‐Turcotte‐Pugh score was significantly improved after 24 months compared to the pretreatment state without difference between the groups. During 24 months of therapy, 15 patients (27.3%) showed antiviral resistance to TBV while no resistance (0%) was reported in the ETV group (P = 0.001). Conclusions Compared to ETV, TBV therapy shows lower efficacy in viral suppression and higher risk of antiviral resistance despite comparable effect on improvement of hepatic function for the treatment of HBV‐related cirrhosis.